2017
DOI: 10.1007/978-3-319-58943-5_63
|View full text |Cite
|
Sign up to set email alerts
|

A Low-Cost Energy-Efficient Raspberry Pi Cluster for Data Mining Algorithms

Abstract: Data mining algorithms are essential tools to extract information from the increasing number of large datasets, also called Big Data. However, these algorithms demand huge amounts of computing power to achieve reliable results. Although conventional High Performance Computing (HPC) platforms can deliver such performance, they are commonly expensive and power-hungry. This paper presents a study of an unconventional low-cost energy-efficient HPC cluster composed of Raspberry Pi nodes. The performance, power and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 14 publications
0
11
0
2
Order By: Relevance
“…A Low-Cost Energy-Efficient Raspberry Pi Cluster for Data Mining Algorithms [6] Raspberry Pi 2 Intel Xeon Phi Data mining algorithms: Association Rule Learning (A priori) and K-Means.…”
Section: Spark Applications Benchmark (Microbenchmarks)mentioning
confidence: 99%
“…A Low-Cost Energy-Efficient Raspberry Pi Cluster for Data Mining Algorithms [6] Raspberry Pi 2 Intel Xeon Phi Data mining algorithms: Association Rule Learning (A priori) and K-Means.…”
Section: Spark Applications Benchmark (Microbenchmarks)mentioning
confidence: 99%
“…Kruger [44] demonstrated that a cluster of Parallella nodes can compete in terms of performance with an Intel i5-3570 server. Similarly, Saffran et al [45] analysed performance and energy consumption of a cluster composed of cost-efficient nodes with a co-processor designed specifically for HPC while executing two Big-Data data-mining algorithms. In [46], the role of SBC-based clusters in energy efficient data centers in the context of big data applications was studied.…”
Section: Single-board Computers As Micro Data-center Serversmentioning
confidence: 99%
“…Several open source microscope designs have been proposed using 3D printing and low cost computing platforms like the Raspberry Pi [7,8,17]. Starting as low as 5$ for a fully featured computer capable of running a desktop version of Linux, the Raspberry Pi allows scientists to use dedicated clusters of computers in virtually any application [18,19,20].…”
Section: Introductionmentioning
confidence: 99%